2018
DOI: 10.17159/2078-5151/2018/v56n3a2075
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus (HIV) infection in men with penile carcinoma is associated with increased prevalence of human papilloma virus infection and younger age at presentation

Abstract: Background: We investigated the prevalence of HIV and human papilloma virus (HPV) infection in men with penile carcinoma. Method: This retrospective study investigated all men with penile carcinoma at the Universitas Academic Hospital in Bloemfontein, South Africa (January 2000-December 2008). Patients' age, HIV status, histological type of carcinoma and evidence of HPV infection were recorded. Statistical analyses included Student's t-test and Fisher's exact test where appropriate (2-tailed p-value < 0.05 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…In Africa, the penile cancer burden is increased by socioeconomic issues, poor knowledge of the disease, poor access to health care, poor access to sanitation and hygiene 3 , low rates of circumcision, and the reduced availability of physical contraceptive methods, such as the male condom, especially in rural areas 37 . The latter is a particular concern in Africa 38 , where a lack of physical contraceptive methods contributes to the spread of both HIV and HPV infections in sub-Saharan Africa countries 37 — the interplay of HIV and HPV increases the incidence of HPV-related malignancies, including penile cancer, and its incidence is up to four times higher in HIV-infected men than in HIV-negative men 39 , 40 .…”
Section: A Need For Collaboration and Centralizationmentioning
confidence: 99%
“…In Africa, the penile cancer burden is increased by socioeconomic issues, poor knowledge of the disease, poor access to health care, poor access to sanitation and hygiene 3 , low rates of circumcision, and the reduced availability of physical contraceptive methods, such as the male condom, especially in rural areas 37 . The latter is a particular concern in Africa 38 , where a lack of physical contraceptive methods contributes to the spread of both HIV and HPV infections in sub-Saharan Africa countries 37 — the interplay of HIV and HPV increases the incidence of HPV-related malignancies, including penile cancer, and its incidence is up to four times higher in HIV-infected men than in HIV-negative men 39 , 40 .…”
Section: A Need For Collaboration and Centralizationmentioning
confidence: 99%
“…11 HIV infection is therefore likely to drive oncogenesis and transformation to PeSCC at an earlier age, a phenomenon also seen in other SCCs, such as those of the cervix and lung. 34 Furthermore, HIV status seems to affect clinical outcomes: HIV increased the risk of mortality from PeSCC four-fold in one study. 22 Conversely, another study found no effect of HIV status (in patients undergoing ART for more than 2 years) on disease characteristics or progression.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of 65 patients with PeSCC, by Wentzel et al, HIV-positive men had a significantly lower age at presentation compared with HIV-negative men (mean difference 13.5 years). 34 Amongst nine case reports and series, data regarding HPV status were included for four patients; 13,17,21 all were of high-risk HPV subtypes, except one. 17 Similarly, in the study by Wentzel et al, HIV-positive men had a higher prevalence of HPV infection, compared to those without HIV (55.6% vs 23.8%).…”
Section: Characteristics Of Pescc Amongst Hiv-positive Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homens que têm parceiras sexuais com neoplasia intraepitelial cervical têm maior incidência de desenvolver neoplasia intraepitelial peniana. Em resumo, a infecção por HIV aumenta as chances de desenvolver CP mesmos em homens mais jovens (Wentzel, 2018).…”
Section: Fatores De Riscounclassified